Nanoribbons of discotic liquid crystal molecules. (2021) - Joshi, Ashutosh; Manjuladevi, V.; Gupta, Raj Kumar; Kumar, Sandeep
Abstract: Discotic liquid crystal molecules are interesting not only due to their mesophases as a function of temperature but also due to their potential to self-assemble into nanostructures. In this article, we facilitate the self-assembly of triphenylene based discotic liquid crystal (TP) molecules in solvent medium to obtain nanoribbons. The flat nanoribbons undergo a morphological transformation to twisted helical nanoribbons due to incorporation of silver nanoparticles. The electrical characterization by measuring current–voltage (I-V) curves from flat and twisted nanoribbons indicated semiconducting behavior. The charge transfer is governed by the classical hopping mechanism. The activation energy reduces due to incorporation of silver nanoparticles in the liquid crystal matrix. The lowest activation energy was found for a doped system of 0.1 wt%.